Sulphated KIT6-Zr as an efficient solid acid catalyst for the production of isosorbide from sorbitol - Ginés-Molina, María José; Santamaría-González, José; Maireles-Torres, Pedro Jesús (My University, 2018)
In recent years, the development of new catalytic processes for the transformation of sugars is converting lignocellulosic biomass in a sustainable and renewable feedstock for the production of biofuels and high value-added chemicals. In this context, the hydrogenation of glucose to sorbitol, and its subsequent double dehydration and cyclization allows to obtain isosorbide. Much attention is being paid in the development of active and selective solid acid catalysts to transform sorbitol into isosorbide. The present work deals with the optimization of different parameters, such as the Si/Zr molar ratio and aging time, in the hydrothermal synthesis of sulphated KIT6. The catalytic activity of the synthesized catalysts was evaluated in the production of isosorbide from molten sorbitol. An isosorbide yield of 58% has been reached at 175 °C after 3 hours of reaction with 10 wt% catalyst. All catalysts have been characterized by various techniques, including X-ray diffraction (XRD), Scanning Electron Microscopy (SEM-EDS), N2 adsorption at -196ºC, X-ray photoelectron spectroscopy (XPS) and the acidity has been measured by NH3-TPD and FTIR of adsorbed pyridine, to elucidate structure-activity relationships.
Keywords: Biomasa; Biomass; Sorbitol; Isosorbide; Heterogeneous catalysis